2019
DOI: 10.1111/ajad.12866
|View full text |Cite
|
Sign up to set email alerts
|

Prescription opioid misuse and comorbid substance use: Past 30‐day prevalence, correlates and co‐occurring behavioral indicators in the 2016 National Survey on Drug Use and Health

Abstract: Background and objectives: Prescription opioid misuse has not been well examined in the context of comorbid substance use in representative samples of substance users. Past 30-day comorbid prescription opioid misuse and recreational substance use (e.g., alcohol, marijuana, cocaine, etc.) was studied in a representative sample of substance users in the United States using the 2016 National Survey on Drug Use and Health (NSDUH). Methods: Prevalence of prescription opioid misuse with and without comorbid substanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 29 publications
1
41
0
Order By: Relevance
“…Examining opioid misuse using nationally representative data, Mojtabai, Amin-Esmaeili, Nejat, & Olfson 22 also found that prescribed-opioid misuse was associated with criminality, mental health distress, and other substance abuse or dependence. Similarly, Grigsby & Howard 23 and found that prescription opioid and polysubstance users had the greatest probability of past-year criminality and mental health distress.…”
Section: Discussionmentioning
confidence: 89%
“…Examining opioid misuse using nationally representative data, Mojtabai, Amin-Esmaeili, Nejat, & Olfson 22 also found that prescribed-opioid misuse was associated with criminality, mental health distress, and other substance abuse or dependence. Similarly, Grigsby & Howard 23 and found that prescription opioid and polysubstance users had the greatest probability of past-year criminality and mental health distress.…”
Section: Discussionmentioning
confidence: 89%
“…Examining opioid misuse using nationally representative data, Mojtabai, Amin-Esmaeili, Nejat, and Olfson [49] also found that prescribed-opioid misuse was associated with criminality, mental health distress, and other substance abuse or dependence. Similarly, Grigsby and Howard [37] and found that prescription opioid and polysubstance users had the greatest probability of past-year criminality and mental health distress. Moreover, Prince [23] found that individuals with opioid misuse disorder who had a severe mental illness were at an increased risk of criminality and suicidality.…”
Section: Discussionmentioning
confidence: 89%
“…In the cases of marijuana dependence or abuse there is a positive relationship with opioid misuse. [37] A more recent review, however, found that medical marijuana use may decrease the probability of opioid use. [39] Campbell et al [39] further revealed that medical cannabis laws may slow the increase of opioid overdose deaths in states with medical cannabis laws compared to states with none.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrent substance use such as nicotine and tobacco dependence [25,26], alcohol [27], sedatives [28], methamphetamines [29], tranquilizers [30][31][32], other analgesics [33], and marijuana [34] have been positively associated with opioid misuse and use disorder [34,35]. Marijuana's association may be context dependent, as it has a mixed relationship with opioid use, misuse, and use disorder.…”
Section: Introductionmentioning
confidence: 99%